POLICY ANALYSIS AND STRATEGY FOR TRADITIONAL MARKET DEVELOPMENTIN CIMAHI CITY - Iman Sulaeman (ASIAN PUBLISHER, 2022)
The autonomy policy has directed the development policy of CimahiCity to improve the standard of living of the community with the potential of the trade and service sector. The policy made by the Government to increase the contribution of the trade sector is to increase traditional market activities. A special program for the development of traditional markets, namely the revitalization of the traditional markets of Pasar Atas Baru, Pasar Cimindi, Pasar Melong and Pasar Citeureup, but the program only caused controversy with traders who were deemed unsuitable for the needs of the place of sale. This study uses three analyzes. Stakeholder analysis was conducted to determine the level of involvement, interest, and influence of all stakeholders involved in traditional market development policies. Descriptive analysis is used to determine the cause of the ineffectiveness of the policy, whether the preparation process is not right or the implementation is not going well. PHA analysis is used to formulate a strategy for developing traditional market rights in Cimahi City so that it can be input for the Regional Government.